PERAN AYAH SEBAGAI SIGNIFICANT OTHER DALAM PENCEGAHAN TERJADINYA LGBT PADA ANAK USIA DINI - Janah, Anwardiani Iftaqul (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
In the process of life, a person is required to perform life activities that do not deviate, so that as human being he/she can beaccepted by the social environment. Various methods and strategies have been strived to prevent LGBT as early as possible, likedetermining personal identity through the fathers’ role in the children lives ,especially in the teachings of gender roles in the familycircle. In fact, there is currently crisis of supervision from parents that tend to ignore the development of gender understandingwithin the children. Recognizing the problem of LGBT (Lesbian, Gay, Bisexual, and Transgender) are importantly connectedwith the development phase of early childhood because at the time children are very easy to absorb information from otherswithout being able to filter them. The role of a mother in a family environment to educate children would not be separated fromthe role of a father as they both have different functions that complement each other. This paper aimed to give further perspectiveof LGBT prevention by strengthening the role of father.